PENGARUH KARAKTERISTIK INDIVIDU DAN FAKTORFAKTOR PEKERJAAN TERHADAP MOTIVASI - Lisdawati (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2019)
Sekolah Tinggi Ilmu Ekonomi Widya Manggala Jalan Sriwijaya No. 32 & 36 Semarang Abstract: This study aimed to determine the influence of individual characteristics and work factors on motivation of employees of CV. Bintang Timur Semarang. In this study, the population was CV. Bintang Timur employees totaled 50 people, including leaders, the entire population was sampled. The analytical tool used in this research was multiple linear regression. The results showed that on the basis of the partial test of the hypothesis with t test results obtained X1 = 3.837; X2 = 15.712; X3 = 7.447; X4 = 2.944; X5 and X6 = 5.436 = 4.869 and 2.012 t table that was in the area of reject Ho, means there was significant influence of motivation, job satisfaction, stress levels, physical work conditions, compensation systems and design work on motivation. While on the test results obtained F value, F = 522.971 > F table 3.232 was in the area of reject Ho, meaning that there was significant influence of individual characteristics and work factors on motivation. The coefficient of determination of both independent variable was 98.50%, it means that the variation of these two variables in explaining the motivation for the remaining 98.50% (100% - 98.50%) = 1.50% was explained by other variables that were not mentioned in the study.